The relationship of design, fabric and seam in developing body contouring jeans / Aisyah Mohd Yasim - Mohd Yasim, Aisyah (2017)
Most Malaysian women who have curvier lower torso area, wish to tighten up the hips to enhance the overall shape. However, many Malaysian women encounter difficulty in finding form fitting jeans that flatter their body shape and smooth out the problematic areas. This study analysed the relationship of fabric, seam and design towards designing body contouring jeans. Hence, examining the potential of body contouring jeans that accentuates their figures besides being stylish and comfortable for daily wear. Post test was conducted whereby 12 respondents having pear type body shaped were interviewed using structured questionnaires. The statistical data were analyzed using SPSS version 20. Besides that, tensile strength test was done using Testometric machine (STM 566) to test on the fabric and seam elongation break (stretch ability), and force break (strength). Preliminary study that included observations and survey questionnaires was conducted to gain information on the preferences of the Malaysian market. Findings from this study showed there is a significant relationship of fabric, seam and design in producing body contouring jeans suitable for Malaysian women. With the production of these attires it will help to enhance the innovation in textile design technology besides establishing good collaboration between the design experts and manufacturing companies.